Anthropology in and of the Archives: Possible Futures and Contingent Pasts. Archives as Anthropological Surrogates - Zeitlyn, D (Annual Reviews, 2012)
Derrida and Foucault provide key starting points to understanding archives. They see archives as hegemonic, characterizing ways of thought, modes of colonization, and the control of citizens. However, they also make clear that archives can be read subversively. With patience, counter-readings allow the excavation of the voices (sometimes names) of subaltern and otherwise suppressed others from the archive. By reading along and across the archival grain, researchers can follow the development of ideas and processes across historical periods. Archives can be seen as orphanages, containing surrogates of performances. Archives (paper and digital) also provide access to the results of anthropological research in ways mandated by ethics codes, but these are subject to controversy. What sorts of consent and what sorts of anonymization should be provided? Archives run by the groups traditionally studied by anthropologists provide models of radical archives that are very different from those conceived of by traditional archivists.